LOW RED FORMATION COLORING REASONS OF CENTRAL IRAN (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
In this article the investigation results of the origin of red pigment of Low Red Formation in Central Iran (Low Oligocene) have been discussed. That is continental and consists of conglomerate, sandstone, marl and claystone. This Formation is unconformably overlain by marine Oligo-Miocene Qum Formation. Mineralogical composition and textural properties of the studied layers show that the Low Red Formation was not red when deposited, although some parts of red pigments were derived from the sedimentory region. This study clearly shows that both detrital and diagenetic pigments contributed in red coloring of the formation but diagenetic processes were more significant.
Keywords: Central Iran; red pigment; Low Red Formation; diagenetic processes